Perencanaan Kelayakan Penambahan Distributed Generator (DG) Terhubung ke Grid untuk Mengurangi Beban Listrik Di PT. JMB - Ritonga, Brilliyan Sanzes; Satria, Habib (Universitas Medan Area, 2024)
PT. JMB has experienced a significant increase in demand for electrical energy in recent years. Factors that might cause this increase include rapid company growth, the use of larger and more complex equipment in company operations, as well as changes in electrical energy patterns and needs in the company's environment. PT. JMB may be very dependent on electricity supply from the PLN grid. Therefore, serious consideration is needed to reduce dependence on electricity supply from PLN by integrating Distributed Generators (DG) as an alternative to maintain smooth company operations. In this planning using ETAP software and the test results produced in the software before using the DG have a voltage on bus 3 of around 0.390 kV and on bus 4 around 0.377 kV while the active power manager room used is 4.1 kW and the reactive power used is 3.62 kVAR while in the director's room and all office rooms have active power, namely, the director's room is 2.61 kW and all office rooms are 1.64 kW in reactive power, namely, the director's room is 2.30 kVAR and all offices are 1.45 kVAR.